Calorie tracking and energy balance: links to body image-related factors and functional impairment in a fitness sample - Slama, Fabián Antonio; Halioua, Robin; Claussen, Malte Christian (Frontiers in Nutrition, 2026)
Calorie tracking refers to the monitoring of daily caloric intake, often pursued for health- or weight-related purposes. Previous studies have found associations between tracking and disordered eating; however, the role of individuals’ energy balance and psychosocial factors remains underexplored. This study examined how tracking behavior and self-reported energy balance are related in a fitness-oriented sample and explored associations with body image-related factors and functional impairment. In an online survey of German-speaking followers of fitness influencers (n = 5,902; 5,480 women, 422 men), participants indicated whether they tracked calories fully or partially and reported their energy balance. They also completed measures of drive for thinness, drive for size, functional impairment, and appearance intolerance. Sex-stratified multinomial logistic regression analyses were conducted to examine associations with tracking. A negative energy balance and drive for thinness were associated with calorie tracking in both sexes, whereas a positive energy balance and drive for size were associated with tracking only among men. Functional impairment was positively associated with tracking in both sexes, whereas appearance intolerance showed no association in men and a negative association in women. These findings align with traditional concerns about body ideals, which underscores the need for a critical evaluation of tracking behavior in clinical and theoretical contexts, particularly in vulnerable groups.